Violence risk assessment and Indigenous Australians: A primer. (March 2018) - Shepherd, Stephane
Violence risk assessment instruments are widely utilised in Australian medico-legal settings to help estimate an individual's level of risk for future violence or offending. This introductory Brief discusses the extant cross-cultural research on risk instruments and the current applicability of the instruments to Australian Indigenous people.